Early childhood caries, dietary habits and nutritional status of toddlers : an intervention study in Kelantan / Ruhaya Hasan - Hasan, Ruhaya (2012)
The aim of this study was to assess the effectiveness of a health promotion intervention program (TIPTOP package) in preventing early childhood caries (ECC), to improve nutritional status and dietary habits among toddlers. The study design was an intervention prospective study and conducted in Tumpat and Pasir Mas districts in Kelantan. The intervention group was 2-3 year old toddlers in Tumpat and received the TIPTOP package, while the control group was in Pasir Mas and received the normal toddlers’ oral health program under the MOH. Baseline information on a proxy population of 527 preschool children (5-6 years old) showed that almost every child in both districts was affected by caries (97.9%) and three-quarters have more than 7 teeth affected by caries. The majority of preschool children had malnutrition; 36.1% who were underweight (WAZ), 40.1% were stunted (HAZ) and one-third (31.1%) were underweight (BMI-for-age). Majority of nutrients intake were not adequate as compared to RNI (2005). Added sugar consumption was three times higher (205.1%) than the recommendation. Dietary habits of sugary foods and drinks showed that “milo” consumption was the highest scored (84.6) followed by “cokelat” (sweets) (75.3) and ice-cream (67.5). More than one-half of parents scored in the “moderate” category of knowledge, attitude and practices. At the intervention phase, 519 of toddlers aged 2-3 years old from Tumpat and Pasir Mas were screened for their caries status and only 15.8% (n=82) were caries free. There was only one drop out and the final sample consists of 40 toddlers from Tumpat and 41 from Pasir Mas who participated until the end of study period. After 18 months, majority of toddlers in intervention group had low or no caries (77.5%),the percentage of caries-free was 37.5%, the odds ratio of having ECC was lower (OR=0.805). About three-quarters (72.5%) had normal of WAZ, more than three-quarters (80%) had normal of HAZ and majority (87.5%) had normal of BMI-for-age. Added sugar intake was reduced, most of sugary foods and drinks consumption improved in intervention than control group. There were improvements in energy, protein, calcium, iron, zinc and vitamin C intake and was a large improvement of fruits and cariostatic foods consumption in intervention group than control group. The majority of mothers’ knowledge scores was high (82.5%), 65% scored high attitude and almost all (95%) had high practices scores. In the control group, only 58.5% had low or no caries, one-third (39%) were normal of WAZ and (34.1%) normal of HAZ and more than one-third (39%) normal of BMI-for-age. Only protein, iron, zinc, vitamin C and vitamin A intake were improved. Added sugar intake increased about one-third. Only one-third (39%) with high knowledge, nearly one-half (43.9%) with high attitude and more than one-half (58.5%) with high practices score at the end of the study period. We conclude that the combination of nutrition and oral health promotion intervention in the TIPTOP program meant to prevent ECC, could have a positive influence in producing good general health outcomes. We recommend that the current Ministry of Health toddlers’ health program should therefore adopt the effective elements of the TIPTOP health promotion package.